The Role of Professional Administrators in Development: The Necessity of Professionalizing Administration in Society - Naser Mirsepasi (مدیریت بهره وری, 2007)
In recent years, there has been a lot of discussion on the ways of adopting appropriate models of development in Iran. Time and again, different views have been voiced on the conflict existing between the priority of the economic development and that of the social justice. These views often carry the implication of state economy as supporting social justice and the market economy as reinforcing economic development. In this paper, following in the footsteps of H. M.'s views, we have claimed that the state economy and the market economy in relation to social justice are not positioned at the ends of the continuum. Rather, they are conflated: the two ends, like the ends of a horseshoe, are much closer to each other. In parallel with this analysis, we have claimed that in the center of the horseshoe, or to put it differently, in between the state economy and the economy of the market there is a key factor to the effect that professionalism in administration can best ensure the interaction between the social justice and economic development. It has also been attempted to put forward the professionalizing concept of management and its establishment laws. In this regard, the selected pattern of the rate of being governmental or freedom of economic system, concerning variables such as political stability and development rate on the one hand, and the existence of bilateral trust in society and professionalism of management on the other hand, offers two matrices for selecting the pattern. According to the frame of the introduced variables which are identified according to this obligatory model, the government's interference in the economic affairs in Iran’s current condition shoud be developed.